On I. A. Bunin’s Story The Date and the Dedication to “M. P. Ch.” - Ivanova, Natalia (Literatūra, 2020)
This article publishes a little-known story by I. A. Bunin in 1902 – The Date – with the dedication “M. P. CH.”, stored in the personal archive of Maria Pavlovna Chekhov. An attempt is made to trace the author’s changes in the story to 1907, which made it possible to remove the dedication and change the original title to Happiness. This edit did not suit Bunin; in Paris he once again changes the text of the story, giving a different name – Dawn All Night. Not only is the text of the story Happiness based on the 1907 collection Korabli, but the place of its publication is specified.
Keywords: Ivan Bunin; Maria Chekhov; the story “The Date”; the story “Happiness”; “Dawn all night”; Russian literature